Analisis Kebutuhan Modul Literasi Budaya: Studi Siswa MI Kelas 4 di Kabupaten Purworejo - Nafi’ah, Siti Anisatun; Elitasari, Handara Tri; Ihtiari, Dhiya Ayu Tsamrotul (Mitra PGMI: Jurnal Kependidikan MI, 2023)
Nowadays, there is a phenomenon where children prefer the culture of other countries rather than their own, for example Korean wafe culture. This study aims to determine the level of students' understanding of Purworejo cultural literacy in class IV students at MI Purworejo. This research method uses quantitative research with a survey approach. Data collection techniques by distributing questionnaires to fourth grade students, interviews with teachers at MI Purworejo and observation. Data analysis techniques using descriptive statistical analysis. Based on the results of the research, it shows that teachers really need a module about Purworejo cultural literacy. Several criteria are needed by teachers and students, namely there are pictures that support the material and the language used is simple and easy to understand. Students added that they wanted modules to be printed in full color, module activities were activities that were active and easy for students to carry. The teacher also wants the material to be adapted to the history and culture of Purworejo.